RANCANG BANGUN APLIKASI SISTEM PAKAR DIAGNOSA PENYAKIT PADA TANAMAN KELAPA SAWIT MENGGUNAKAN METODE FORWARD CHAINING BERBASIS WEB - Bambang Hermanto; Albertus Sudirman; Nabilla Tsamara (Jurnal Pepadun, 2020)
This research aims to develop an expert system application that can facilitate users in diagnosing oil palm plant diseases based on symptoms. The data used in this expert system consists of 7 diseases and 12 symptoms of oil palm plants. Expert system that is built on web-based using a rule with the Forward Chaining method to identify diseases. Testing has been done in two stages. They are internal testing and external testing. Internal testing consists of functional testing and system expertise testing. Functional testing using the Black Box method with the Equivalence Patitioning (EP) technique shows that the developed system functions as expected. Expertise testing is done by comparing the results of the diagnosis by the system and the results of the diagnosis by experts to produce a diagnosis of system expertise as expected. External testing is done by giving questionnaires to 23 respondents who were divided into 2 groups to get an assessment of the system. The questionnaire results of the group I (Experts) obtained a satisfaction value of 81%, while the group II (Students of the Department of Plantation Cultivation) obtained a satisfaction value of 75%.